La «Passio s. Mammetis m. Caesareae Cappadociae» en las compilaciones hagiográficas de Rodrigo de Cerrato (OP) y Juan de Gil de Zamora (OFM = The «Passio S. Mammetis M. Caesareae Cappadociae» In The Hagiographical Compilations Of Rodrigo De Cerrato (Op) And Juan Gil De Zamora (Ofm) - Martín, José Carlos (Hagiographica, 2023)
This article reviews the Latin hagiographic corpus in honour of Saint Mames of Caesarea and studies its reception in the Latin hagiographical compilations of Hispania in the 13th century: those of Bernardo de Brihuega, Rodrigo de Cerrato and Juan Gil de Zamora. Brihuega’s text has been lost, but those written by the Cerratense and Gil de Zamora, both inspired by the version of the so-called Pasionario Hispánico, have survived to the present day. The article also offers the first critical edition of the abbreviation included by Rodrigo de Cerrato in his Vitas sanctorum and the edition princeps of the one written by Juan Gil de Zamora in his Armarium scripturarum.